Low-density medium-strength high-modulus aluminum lithium alloy and preparation method thereof
By adjusting the composition and process of aluminum-lithium alloy, low-density medium-strength and high-mode aluminum-lithium alloys are prepared, which solves the problems of high density and insufficient stiffness in the aerospace field of existing materials, and achieves lighter and lower-cost material performance.
Patent Information
- Application Number
- CN202411750385.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-28
AI Technical Summary
Existing aluminum-lithium alloy materials have not yet met the needs of lower density, higher stiffness and better damage resistance in the aerospace field.
By adjusting the composition of aluminum-lithium alloy, increasing the Li element content, adjusting the Cu and Mg content, and controlling the Cu:Mg ratio between 1.38 and 3.5, microalloy elements such as Zr, Ti, Mn are added at the same time. Multi-component design, multi-stage homogenization process and deformation heat treatment process are used to prepare low-density, medium-strength and high-mode aluminum-lithium alloys.
The density of aluminum-lithium alloy is reduced to <2.60g/cm3, the elastic modulus is increased to >76GPa, and the tensile strength reaches the level of 450MPa to 500MPa, meeting the demand for lightweight materials in the aerospace field, while reducing material costs.
Smart Images

Figure CN119710399A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to a high-performance aluminum-lithium alloy material preparation process, and relates to a low-density, medium-strength, high-modulus aluminum-lithium alloy and a preparation method thereof. Background Art
[0002] The use of low-density, high-rigidity aluminum-lithium alloy materials is one of the important measures to achieve structural weight reduction in the aviation and aerospace fields. As a load-bearing component wrapped outside the fuselage frame, the fuselage skin plays the role of bearing and transmitting aerodynamic loads. The force conditions during flight are complex and require high dimensional accuracy. In order to meet the above requirements and control costs, the fuselage and wing skins of civil passenger aircraft all use medium-strength aluminum alloy materials with good damage resistance. In order to further achieve the effect of structural weight reduction and life extension, the use of aluminum-lithium alloy sheets with higher rigidity, lower density and better damage resistance as fuselage skins has become an important development trend. Among the many aluminum-lithium alloys, Al-Cu-Li-X alloys have the characteristics of damage resistance, high specific strength, and high specific modulus. By using special rolling and precision deformation heat treatment processes, plates with excellent comprehensive properties such as good strength, fracture toughness, corrosion resistance and damage resistance can be obtained. It is one of the important choices for aluminum alloy materials for civil passenger aircraft skins.
[0003] At present, the lithium content of mature Al-Cu-Li-X thin plates at home and abroad is in the range of 0.9-1.5wt%, and the density of the plates is generally 2.67-2.72g / cm 3 The elastic modulus is in the range of 74-77GPa, which is a certain improvement over traditional aluminum alloys, but it still fails to give full play to the characteristics of aluminum-lithium alloys. In order to further meet the needs of weight reduction of fuselage skin materials, it is urgent to develop new aluminum-lithium alloys with lower density, higher stiffness (elastic modulus) and certain strength.
[0004] Chinese patent CN 202011609779.9 proposes an ultra-low density aluminum-magnesium alloy. The high content of magnesium and lithium makes the alloy density only 2.3g / cm 3 , but its tensile strength is low (less than 400MPa). Chinese patent CN202110965607.3 proposes a lower density Al-Li alloy, which adds rare earth beryllium elements to refine the grains and improve the alloy strength, but it will significantly increase the material cost and is not suitable for industrial preparation and application. Summary of the invention
[0005] The purpose of the present invention is to propose a low-density, medium-strength, high-modulus aluminum-lithium alloy and a preparation method thereof in response to the demand for weight reduction of aerospace skin materials, so that the prepared Al-Cu-Li aluminum-lithium alloy has a low density (<2.67g / cm 3), medium strength (<500MPa) and high elastic modulus (>76GPa) performance characteristics.
[0006] To solve this technical problem, the technical solution of the present invention is:
[0007] On the one hand, a low-density, medium-strength and high-modulus aluminum-lithium alloy is provided, wherein the components and their mass percentages of the aluminum-lithium alloy are: Cu 2.1-2.9%, Mg 0.8-1.9%, Li 1.2-2.2%, Zn 0.15-0.45%, Zr 0.06-0.10%, Mn 0.3-0.6%, Ti 0.02-0.05%, impurity elements Si≤0.10%, Fe≤0.10%, other impurities individually ≤0.05%, the total amount ≤0.15%, and the balance is Al.
[0008] Furthermore, the components and their mass percentages of the aluminum-lithium alloy are: Cu 2.2-2.8%, Mg 0.8-1.6%, Li 1.5-2.0%, Zn 0.15-0.45%, Zr 0.06-0.10%, Mn 0.3-0.6%, Ti 0.02-0.05%, impurity elements Si≤0.10%, Fe≤0.10%, other impurities individually≤0.05%, total amount≤0.15%, and the balance is Al. The Cu:Mg ratio is 1.38-3.5.
[0009] In the preferred technical solution, the components of the aluminum-lithium alloy and their mass percentages are: Cu 2.4-2.6%, Mg 1.0-1.4%, Li 1.6-1.9%, Zn 0.15-0.45%, Zr 0.06-0.10%, Mn 0.3-0.6%, Ti 0.02-0.05%, impurity elements Si≤0.10%, Fe≤0.10%, other impurities individually ≤0.05%, total ≤0.15%, and the balance is Al. The Cu:Mg ratio is 1.7-2.6.
[0010] On the other hand, a method for preparing the low-density medium-strength high-modulus aluminum-lithium alloy is provided, and the preparation method comprises the following steps:
[0011] Step 1: Melting and casting according to the alloy composition to prepare a semi-continuous ingot;
[0012] Step 2: homogenizing the ingot, using a two-stage heating process;
[0013] Step 3: After the homogenized ingot is peeled / milled, it undergoes primary thermal deformation → medium temperature insulation → medium temperature secondary thermal deformation;
[0014] Step 4: The material after heat treatment is subjected to solution quenching, cold deformation and aging treatment to obtain a low-density, medium-strength and high-modulus aluminum-lithium alloy plate.
[0015] The double-stage homogenization in step 2 is specifically as follows: the temperature of the first stage is 380°C to 430°C, and the temperature of the second stage homogenization is 485°C to 510°C.
[0016] In step 3, the hot deformation treatment process adopts hot rolling or hot forging process. The initial hot rolling / hot forging heating temperature is 400℃~420℃, and the initial hot deformation is 1.5~1.7 times the thickness of the finished product; medium temperature insulation is 390℃~400℃, insulation for 2~4h; medium temperature secondary hot forging / hot rolling is carried out after the furnace is taken out until the thickness specification of the finished product is reached. The initial hot deformation is 1.5~1.7 times the thickness of the finished product because the deformation between the original ingot size and the finished product is too large, and cracking may occur in the first deformation. At the same time, the large temperature difference between the surface temperature and the core of the casting during the first hot deformation will also cause deformation cracking. Therefore, choosing medium temperature insulation + secondary hot deformation can minimize the problem of deformation cracking.
[0017] The solution treatment in step 4 is a two-stage solution treatment, first at 470-490°C for 0.5-3h, then heated to 520-540°C, kept for 0.5-4h, quenched in water at room temperature, and then cold deformed by 4.5%-6.5% within 30min. Adding cold deformation after solution quenching can increase the number of dislocations in the aluminum-lithium alloy of the present invention and effectively improve the strength of the alloy. T8 artificial aging = solution quenching + cold deformation + aging treatment. The deformation between 4.5% and 6.5% is the most effective range for improving strength. Excessive cold deformation has the risk of fracture.
[0018] The aging treatment process used in step 4 is a double-stage aging treatment, and the aging process is to keep the temperature at 120-130°C for 6-10 hours, heat up to 145-155°C with the furnace, and keep the temperature for 12-20 hours.
[0019] Preferably, the cold deformation in step 4 is performed by using a stretching machine for pre-stretching deformation or a press for cold pressing deformation.
[0020] The beneficial effects of the present invention are:
[0021] Aiming at the further use demand of lightweight materials in the aerospace field, the present invention invents an Al-Cu-Li aluminum alloy and its preparation process, and controls the Cu:Mg ratio between 1.38 and 3.5 by increasing the Li element content and adjusting the Cu and Mg contents. (Too high a ratio will lead to reduced alloy toughness and increased density, while too low a ratio cannot guarantee the strength and hardness of the alloy, see the specific embodiment), and at the same time, micro-alloying elements such as Zr, Ti, and Mn are added in combination to refine the grains and control recrystallization, thereby improving the mechanical properties of the alloy.
[0022] 1. The present invention can obtain a density of less than 2.60g / cm through multi-component design, multi-stage homogenization process, deformation heat treatment and other processes. 3 , elastic modulus> 76GPa, while the tensile strength reaches 450MPa ~ 500MPa level of low-density, high elastic modulus medium-strength aluminum-lithium alloy, if used in fuselage skin materials will have the advantages of lighter weight and lower cost.
[0023] 2. The preparation process of the present invention is simple and feasible, convenient for industrial mass production, and can be realized on existing industrial equipment, with strong operability and feasibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions implemented in the present invention, the following is a brief explanation of the drawings required to be used in the examples of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 The mechanical properties and physical properties of the alloy of the present invention are compared with those of existing alloys. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] The features of various aspects of the embodiments of the present invention will be described in detail below. In the detailed description below, many specific details are proposed to fully understand the present invention. However, it is obvious to those skilled in the art that the present invention can also be implemented without these specific details. The following description of the embodiments is only for a better understanding of the present invention by illustrating examples of the present invention. The present invention is not limited to any specific settings and methods provided below, but covers all product structures, any improvements, replacements, etc. of methods covered without departing from the spirit of the present invention.
[0028] In the various drawings and the following description, well-known structures and techniques are not shown to avoid unnecessarily obscuring the present invention.
[0029] Typical compositions of the alloy of the present invention are shown in Table 1 (wt %).
[0030] Table 1 Experimental alloy composition (wt%)
[0031] serial number Cu Mg Li Zr Mn Zn Ti Si Fe Cu:Mg 1# 2.11 0.85 1.23 0.12 0.31 0.21 0.06 0.10 0.10 2.48 2# 2.23 1.03 1.56 0.12 0.32 0.21 0.06 0.10 0.10 2.17 3# 2.93 1.00 1.94 0.11 0.31 0.20 0.06 0.10 0.10 2.93 4# 2.64 1.63 2.00 0.12 0.31 0.22 0.06 0.10 0.10 1.61 5# 2.53 1.09 1.63 0.13 0.30 0.22 0.06 0.10 0.10 2.32 6# 2.60 1.49 1.99 0.11 0.30 0.21 0.06 0.10 0.10 1.74 7# 2.40 1.03 1.50 0.13 0.31 0.22 0.06 0.10 0.10 2.33 8# 2.55 1.30 1.85 0.11 0.30 0.21 0.06 0.10 0.10 1.96 9# 2.53 1.58 1.68 0.11 0.32 0.20 0.06 0.10 0.10 1.60 10# 2.58 1.55 1.88 0.11 0.31 0.20 0.06 0.10 0.10 1.66
[0032] Example 1
[0033] Alloy compositions 5# and 10# in Table 1 (wherein the Cu:Mg ratios were 2.32 and 1.66, respectively) were prepared, and their performance was compared with the typical third-generation aluminum-lithium alloy 2060 as a reference alloy.
[0034] According to the 5# or 10# alloy composition in Table 1, smelting and casting are performed to prepare semi-continuous ingots;
[0035] The Φ360 mm ingot was placed in an air circulation furnace for two-stage homogenization, the first stage: 410°C / 10h, the second stage: 500°C / 22h;
[0036] The homogenized ingot is peeled, heated at 410℃±10℃, and then taken out of the furnace for free forging. After two piercing and two drawing, it is prepared into a forging with a thickness of 130mm. The forging is placed in an air circulation furnace for heating and kept at 400℃ for 4h. It is taken out of the furnace for medium-temperature secondary hot forging with a final forging temperature of 305℃ to forge into a forging with a thickness of 80mm.
[0037] The forgings are placed in a box-type quenching furnace for solution quenching treatment. The solution process is: keep at 470℃ for 4h, then heat up to 520℃, keep for 2h, quench in room temperature water, and the forgings after quenching are cold compressed with a compression deformation of 6.0%; the forgings after cold pressing and stretching are subjected to double-stage artificial aging treatment. The aging process is to keep at 125℃ for 10h, then heat up to 145℃ with the furnace and keep for 14h.
[0038] The element contents and weight percentages of the comparative alloy 2060 are as follows: Cu 3.94%, Mg 0.68%, Li 0.76%, Mn 0.3%, Zn 0.5%, Mn 0.3%, Zr 0.12%, Ti 0.06%, Fe 0.05%, Si 0.05%, and its Cu:Mg ratio is 5.8.
[0039] The performance comparison between the alloy of Example 1 and the comparative alloy is shown in Table 2.
[0040] Table 2 Comparison of room temperature tensile properties and physical properties of alloy forgings
[0041] state direction alloy <![CDATA[R m / MPa]]> <![CDATA[R 0.2 / MPa]]> A% E <![CDATA[ρ / g / cm 3 ]]> T852 Vertical 5# 499 435 11.4 77 2.58 T852 Vertical 10# 487 420 13.8 78 2.58 T852 Vertical 2060 470 423 13.7 73 2.70
[0042] Example 2
[0043] The compositions of alloy #3 and alloy #7 in Table 1 (wherein the ratios of Cu:Mg are 2.93 and 2.33, respectively) were prepared, and their performance was compared with the typical third-generation aluminum-lithium alloy 2060 as a reference alloy.
[0044] According to the composition of alloy 3# and alloy 7# in Table 1, they are melted and cast to prepare semi-continuous ingots;
[0045] The 280mm thick ingot is placed in an air circulation furnace for two-stage homogenization, the first stage: 410℃ / 10h, the second stage: 500℃ / 20h; the ingot after homogenization is peeled, heated at 410℃±10℃, then taken out of the furnace and hot rolled once to prepare a rolled plate with a thickness of 90mm, the rolled plate is placed in an air circulation furnace for heating, kept at 400℃ for 4h, taken out of the furnace for medium-temperature secondary hot rolling, the final forging temperature is 310℃, and forged into a rolled plate with a thickness of 50mm.
[0046] The rolled plate is placed in a box-type quenching furnace for solution quenching treatment. The solution process is: keep at 470℃ for 2.5h, then heat up to 520℃, keep for 1.5h, quench in room temperature water, and the quenched plate is cold stretched with a stretching deformation of 5.0%; the plate after cold stretching is subjected to double-stage artificial aging treatment. The aging process is to keep at 125℃ for 10h, then heat up to 145℃ with the furnace and keep for 14h.
[0047] A typical third-generation aluminum-lithium alloy 2060 was selected as a comparison alloy. The element content and weight percentage of the 2060 alloy were selected as follows: Cu 3.94%, Mg 0.64%, Li 0.99%, Mn 0.3%, Zn 0.5%, Mn 0.3%, Ag 0.25, Zr0.12%, Ti 0.06%, Fe 0.05%, Si 0.05%, and the Cu:Mg ratio was 6.15.
[0048] The room temperature mechanical tensile properties and physical properties of the alloy were measured and compared with those of the comparative alloy, and the performance results are shown in Table 3. By comparing the 3# alloy and the 7# alloy, it can be found that when the Cu:Mg ratio is less than 3.5, the strength of the 7# alloy is more advantageous when the Cu:Mg ratio is less than 2.6.
[0049] Table 3 Room temperature tensile properties and physical properties of alloy plates
[0050] state direction alloy <![CDATA[R m / MPa]]> <![CDATA[R 0.2 / MPa]]> A% E <![CDATA[ρ / g / cm 3 ]]> T8 Vertical 3# 480 428 12.5 78 2.59 T8 Vertical 7# 495 440 10.9 78 2.59 T8 Vertical 2060 475 426 12.6 73 2.70
[0051] In addition, by studying the physical properties of the alloys of the present invention, it can be found that: 1) the density of the two alloys selected by the present invention is 2.58g / cm 3 , compared with the 2060 alloy density of 2.70g / cm 3Compared with a decrease of 4%, the elastic modulus of the alloy of the present invention is 77-78 GPa, which is 4-5 GPa higher than the elastic modulus of 73 GPa of the comparative alloy.
[0052] 2) In terms of mechanical properties, the Cu content in the alloy will lead to a decrease in the strength of the alloy, but the alloy of the present invention is slightly improved compared with the comparative alloy. This is because the Cu:Mg ratio in the comparative alloy is too large (above 5), and the T8 aging precipitation phase of the alloy is mainly the θ′ phase (Al2Cu). When the Cu:Mg ratio is less than 3.5, the T8 aging precipitation phase of the alloy of the present invention is mainly the T1 phase (Al2CuLi), and the strengthening effect of the T1 phase is stronger than that of the θ′ phase, especially when the Cu:Mg ratio is less than 2.6, which can effectively compensate for the aging strength.
[0053] The performance of the alloy prepared as a thick plate, that is, Example 2, is compared and found to be consistent with that of Example 1. While ensuring the mechanical properties of the alloy, the elastic modulus and density of the alloy of the present invention are advantageous.
[0054] Therefore, the alloy of the present invention adopts the method of reducing the Cu content and increasing the Mg content to reduce the alloy density and improve the alloy elastic modulus at the same time. By controlling the appropriate Cu:Mg ratio to change the type of alloy aging precipitation phase, the mechanical properties of the alloy in the aging state can be effectively guaranteed. In particular, for the weight reduction needs of aerospace skin materials, the alloy has the best comprehensive performance when the Cu:Mg ratio is 1.6-2.6.
[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the field can easily think of various equivalent modifications or substitutions within the technical scope disclosed by the present invention, and these modifications or substitutions should all be covered within the protection scope of the present invention.
Claims
1. A low-density, medium-strength, high-modulus aluminum-lithium alloy, characterized in that: The components of the aluminum-lithium alloy and their mass percentages are: Cu 2.1-2.9%, Mg 0.8-1.9%, Li 1.2-2.2%, Zn 0.15-0.45%, Zr 0.06-0.10%, Mn 0.3-0.6%, Ti 0.02-0.05%, impurity elements Si≤0.10%, Fe≤0.10%, other impurities individually≤0.05%, the total amount≤0.15%, and the balance is Al.
2. The low-density, medium-strength, high-modulus aluminum-lithium alloy according to claim 1, characterized in that: The components and their mass percentages of the aluminum-lithium alloy are: Cu 2.2-2.8%, Mg 0.8-1.6%, Li 1.5-2.0%, Zn 0.15-0.45%, Zr 0.06-0.10%, Mn 0.3-0.6%, Ti 0.02-0.05%, impurity elements Si≤0.10%, Fe≤0.10%, other impurities individually≤0.05%, total amount≤0.15%, and the balance is Al. The ratio of Cu:Mg is 1.38-3.
5.
3. The low-density, medium-strength, high-modulus aluminum-lithium alloy according to claim 1, characterized in that: The components and their mass percentages of the aluminum-lithium alloy are: Cu 2.4-2.6%, Mg 1.0-1.4%, Li 1.6-1.9%, Zn 0.15-0.45%, Zr 0.06-0.10%, Mn 0.3-0.6%, Ti 0.02-0.05%, impurity elements Si≤0.10%, Fe≤0.10%, other impurities individually≤0.05%, total amount≤0.15%, and the balance is Al. The ratio of Cu:Mg is 1.7-2.
6.
4. A method for preparing the low-density, medium-strength and high-modulus aluminum-lithium alloy according to claim 1, characterized in that: The preparation method comprises the following steps: Step 1: Melting and casting according to the alloy composition to prepare a semi-continuous ingot; Step 2: homogenizing the ingot, using a two-stage heating process; Step 3: After the homogenized ingot is peeled / milled, it undergoes primary thermal deformation → medium temperature insulation → medium temperature secondary thermal deformation; Step 4: The material after heat treatment is subjected to solution quenching, cold deformation and aging treatment to obtain a low-density, medium-strength and high-modulus aluminum-lithium alloy plate.
5. The preparation method according to claim 4, characterized in that: The double-stage homogenization in step 2 is specifically as follows: the temperature of the first stage is 380°C to 430°C, and the temperature of the second stage homogenization is 485°C to 510°C.
6. The preparation method according to claim 4, characterized in that: In step 3, the process of heat deformation treatment adopts hot rolling or hot forging process. The initial hot rolling / hot forging heating temperature is 400℃~420℃, and the initial heat deformation amount is 1.5~1.7 times the thickness of the finished product; medium temperature insulation is 390℃~400℃, and insulation is carried out for 2~4h; after taking out of the furnace, medium temperature secondary hot forging / hot rolling is carried out until the finished product thickness specification is reached.
7. The preparation method according to claim 4, characterized in that: The solution treatment in step 4 is a two-stage solution treatment, firstly keeping the temperature at 470-490°C for 0.5-3h, then heating to 520-540°C, keeping the temperature for 0.5-4h, quenching in water at room temperature, and then performing a cold deformation treatment of 4.5%-6.5% within 30min.
8. The preparation method according to claim 4, characterized in that: The aging treatment process used in step 4 is a double-stage aging treatment, and the aging process is to keep the temperature at 120-130°C for 6-10 hours, heat up to 145-155°C with the furnace, and keep the temperature for 12-20 hours.
9. The preparation method according to claim 4, characterized in that: The cold deformation method in step 4 adopts a stretching machine for pre-stretching deformation.
10. The preparation method according to claim 4, characterized in that: The cold deformation method in step 4 is to use a press to perform cold deformation.
Citation Information
Patent Citations
An ultra-low density aluminum-lithium alloy and its preparation method
CN112853172B
Low-density high-modulus high-strength aluminum alloy and preparation method thereof
CN113621854A